Microbial Resistance Movements: An Overview of Global Public Health Threats Posed by Antimicrobial Resistance, and How Best to Counter - Dhingra, Sameer; Rahman, Nor Azlina A.; Peile, Ed; Rahman, Motiur; Sartelli, Massimo; Hassali, Mohamed Azmi; Islam, Tariqul; Islam, Salequl; Haque, Mainul (Frontiers in Public Health, 2020)
Antibiotics have changed medical practice by significantly decreasing the morbidity and mortality associated with bacterial infections in human beings and animals. However, infectious diseases remain the leading cause of death in the world. There is global concern about the rise in antimicrobial resistance (AMR) which affects both developed and developing countries. AMR is a public health challenge with extensive health, economic and societal implications. This paper sets AMR in context starting with the history of antibiotics including the discovery of penicillin and the golden era of antibiotics, before exploring the problems and challenges we now face due to AMR. Among the factors discussed are the low level of development of new antimicrobials and the irrational prescribing of antibiotics in developed and developing countries. A fundamental problem is the knowledge, attitude, and practice (KAP) regarding antibiotics among medical practitioners, and we explore this aspect in some depth, including a discussion on the KAP among medical students. We conclude with a few suggestions on how to address this public health threat, including recommendations on training medical students about antibiotics, and strategies to overcome the problems of irrational antibiotic prescribing and AMR.